Assessing and giving feedback to students’ written work: Closing the gap between expert and novice raters - Jerry, Clarence; Jan, Jariah Mohd.; Samuel, Moses (Journal of Modern Languages, 2017)
The present study focuses on the feasibility of narrowing the gap in the differences between expert and novice raters in terms of expertise in assessing and evaluating writing in a training/workshop through the use of a tentative mental model which was developed in a prior research. The conceptual mental model of assessing writing deployed in this study helped the researchers to understand how expert raters could be differentiated from the novice raters in terms of their mental cognitive processes. This paper reports the understanding which was translated into a training module and trialled out in the workshop. Five participants out of twenty five course participants who came for the workshop were interviewed and the preliminary probe into the usefulness of the mental model in training yielded positive results. The findings of this study indicated that with proper intervention, beginning teachers can be trained to be â€œexpert ratersâ€ themselves by closely following the tentative mental model recommended in the study